A Study of the Maya Tribes in the Americas - Noori, Sima (Journal of Natural Sciences – Kabul University, 2021)
The origins of the ancient Maya civilization trace back to 2000 BC. The Mayans inhabited regions of what is now southern Mexico. They typically constructed their cities in the heart of rainforests. The Maya people developed the first writing system in the Americas during the 3rd century BC, which comprised 800 characters. The Mayans acquired mathematical knowledge, partly influenced by the Olmec tribes, and are believed to be the first people in the world to conceptualize zero. Researchers attribute the decline of the Maya civilization to factors such as overpopulation, unfavorable weather conditions, warfare, shifting trade routes, and drought. This paper aims to introduce Native American ethnic groups and shed light on their pre-Columbian civilizations. It is particularly relevant for students in geography, geology, archaeology, social sciences, and other fields, as well as for those interested in understanding these historically significant cultures.